PENGARUH GREEN MARKETING DAN CUSTOMER RELATIONSHIP MANAGEMENT TERHADAP LOYALITAS ANGGOTA KOPERASI DIMEDIASI OLEH KEPUASAN ANGGOTA - Afriansyah Fauzi, Egi; Suroso, Edy (Penerbit Lafadz Jaya, 2025)
The purpose of this research was to analyze the role of cooperative member satisfaction in mediating the influence of green marketing and customer relationship management on the cooperatif member loyalty of Minalaka Islamic Boarding School in Tasikmalaya City. The research method used is a quantitative survey method. Data was obtained directly through a questionnaire to 145 respondents taken from cooperative members of the Minalaka Islamic Boarding School in Tasikmalaya City. The data analysis technique used in this research is Partial Least Squares-Structural Equation Modeling (PLS-SEM). From the results of this research, it was found that green marketing has a significant effect on member satisfaction and cooperatif members loyalty. Customer relationship management has a significant effect on member satisfaction and cooperatif members loyalty. Cooperative members satisfaction has a significant effect on cooperatif members loyalty. Cooperative members satisfaction can mediate the influence of green marketing and customer relationship management on cooperatif members loyalty. The findings in this research provide an overview that the implementation of green marketing and customer relationship management is an effective strategy to increase member satisfaction and member loyalty in the context of Islamic Boarding School Cooperatives.